2018
DOI: 10.3390/ijms19082216
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Genome-Wide Analysis of Chitin-Binding Proteins Gene Family in Pepper (Capsicum annuum L.) and Transcriptional Regulation to Phytophthora capsici, Abiotic Stresses and Hormonal Applications

Abstract: Chitin-binding proteins are pathogenesis-related gene family, which play a key role in the defense response of plants. However, thus far, little is known about the chitin-binding family genes in pepper (Capsicum annuum L.). In current study, 16 putative chitin genes (CaChi) were retrieved from the latest pepper genome database, and were classified into four distinct classes (I, III, IV and VI) based on their sequence structure and domain architectures. Furthermore, the structure of gene, genome location, gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 95 publications
1
45
0
1
Order By: Relevance
“…Annotation of these specific genes showed various functions (Tables S14, S15), but they were particularly overrepresented in the chitin-related Gene Ontology (GO) categories. Chitin-binding genes are known as a pathogenesis-related gene family, which plays a fundamental role in the defense response of plants [38, 39]. This finding suggests possible response roles, related to biotic stress, in eggplant.…”
Section: Resultsmentioning
confidence: 99%
“…Annotation of these specific genes showed various functions (Tables S14, S15), but they were particularly overrepresented in the chitin-related Gene Ontology (GO) categories. Chitin-binding genes are known as a pathogenesis-related gene family, which plays a fundamental role in the defense response of plants [38, 39]. This finding suggests possible response roles, related to biotic stress, in eggplant.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, the evolutionary relationship between CaChiVI2 and pepper CBP homologs in other species was based on phylogenetic analysis (Ali et al, 2018). The analysis revealed that pepper CBP could be classified into four main classes with potentially similar functions.…”
Section: Cloning and In Silico Analysis Of Pepper Cachivi2mentioning
confidence: 85%
“…The total-RNA was extracted as explained in our recently published papers (Ali et al, 2018;Khan et al, 2018). The first chain was synthesized by the Primer Script TM Kit (TaKaRa, Dalian, China).…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
See 2 more Smart Citations